Греческая церковь Иоанна Предтечи в Керчи (третья четверть XVIII – начало XX вв.) - Пономарев, Л.Ю.; Бейлин, Д.В.; Бейлина, С.А. (Археологический альманах, 2012)
In 1774 Kerch, in obedience to the terms of Kuchuk-Kaynardzhi agreement, stepped back to the Russian empire. First decades an only one orthodox temple functioned in town. In official records already from 70-th XVIII c. they began to be named the church of Ioann Predtecha. At the same time the name – «Greek church» a foothold after him. In 1800–1804 it was reconstructed, finishing building western pridel with galleries and bell tower. In 1835 north pridel was erected. By the end of XIX с. since a new bell tower with pritvor and north pridel were erected, the architectural band of church was formed finally. After 1920 the belongings churches of building and cerkovno-prikhodskie schools were closed. To the 30-years church falling into a decay and was finally closed on December, 28, 1937.